Investigation of α-Amylase and α-Glucosidases Inhibitory Effects of Silybum marianum (L. Gaertn) Seed Extracts In Vitro - H Fallah Huseini; B Asghari; J Asgarpanah; T Eghbali Zarch; A Babai Zarch (Institue of Medicinal Plants, ACECR, 2012)
Background: The α-glucosidase and α-amylase are the key enzymes involved in broken down of dietary polysaccharides to monosaccharides or simple sugars molecules. Inhibition of these two gastrointestinal enzymes especially in diabetic patients can reduce glucose absorption and decreases postprandial hyperglycemia.   Objective: The present study was undertaken to explore the α-glucosidase and α-amylase inhibitory effects of different silybum marianum seed extracts.   Methods : Silybum marianum seeds were collected from the Institute of Medicinal Plants farm and total extract and different fractions were prepared by methanol, chloroform, hexane and ethyl acetate solvents. The inhibitory effects of the extracts were tested on α -amylase and α -glucosidase enzyme separately. In this experiment, the minimum concentration of the extract required for 50% inhibition of enzyme activity (IC50), was obtained and compared with acarbose as a positive control.   Results : The results showed that total methanol extract and hexane, chloroform, ethyl acetate and methanol fractions of silybum marianum seeds have inhibitory effects on α -amylase and α -glucosidase enzyme activity. Statestical analysis showed that total methanol extract of silybum marianum seeds have stronger inhibitory effect than other fractions on α -amylase and α -glucosidase enzyme activity compared to acarbose. Conclusion : Methanol extracts of silybum marianum seeds have stronger inhibitory effect than methanol, ethyl acetate, hexane and chloroform fraction on α -amylase and α -glucosidase enzyme activity.